Personalized treatment in localized pancreatic cancer - Neoptolemos, John P.; Hu, Kai; Bailey, Peter; Springfeld, Christoph; Cai, Baobao; Miao, Yi; Michalski, Christoph; Carvalho, Carlos; Hackert, Thilo; Büchler, Markus W. (European surgery, 2023)
The treatment elements used for pancreatic ductal adenocarcinoma (PDAC) include surgical resection, systemic cytotoxic agents, and targeted drugs. For second- and third-line therapies in PDAC, approximately 15% of patients have actionable mutations although only 2.5% receive matched targeted treatment but with a significant improvement in survival of around 16 months. For the majority of PDAC patients the current most effective strategy is surgical resection of the primary tumor and systemic combination chemotherapy. The chemotherapy regimens and the order of delivery relative to the resection reference point have been based to a large extent on randomized trials using a newly developed empirical staging (Em) system. Although the reductionist TNM based AJCC and UICC systems work well for pathology staging, they are less accurate and less manageable for treatment decision-making. This Em system defines locally resectable (EmR), borderline resectable (EmBR), and unresectable (EmUR) stages, plus the emerging entity of oligometastatic disease (EmOm). For EmR patients, 6 months of adjuvant chemotherapy achieves 5‑year survival rates of 30-50%. In EmBR short-course (2 months) neoadjuvant plus 6‑month adjuvant chemotherapy increases 12-month survival rates to around 77%, compared to 40% for upfront surgery, despite resection rates of 64-85% and 75%, respectively. Longer-course (4 months) neoadjuvant chemotherapy has also been shown to achieve an 18-month overall survival of 67%. In EmUR, induction therapy (3-6 months) may result in resections rates of 20-60% with significantly improved survival rates compared to no resection. For all stages including the polymetastatic (EmPm) setting, patients with good performance status receive combination chemotherapies based on either oxaliplatin (FOLFIRINOX or NALIRIFOX) or gemcitabine (GEM-CAP, or Gem-NabP). Molecular subtypes (Moffitt, Collisson, Bailey, and Cheng-Sen-Yue) are shown to be associated with treatment responses. Transcriptomic signatures have also been developed as classifiers for determining either oxaliplatin- or gemcitabine-based therapies (PurIST, Tiriac, GemPred+, and ESPAC) and are being evaluated in various studies. Most notably the ESPAC transcriptomic signature is being used as the treatment classifier in the experimental arms of the randomized ESPAC6 adjuvant trial in EmR patients and the ESPAC7 induction therapy trial in EmUR patients. Genomic and transcriptomic profiling at baseline and over time is an integral part of ESPAC6/7 to deepen our understanding of tumor plasticity during the course of therapy, identifying the intrinsic (persister cell) and acquired (genetic) tumor plasticity evolving over time and in reaction to different therapies in order to enable a scientific approach to overcoming clonal-resistance clades.
Online veröffentlicht: 02. Oktober 2023
Gesehen am 05.12.2023